المجتمعات الإسلامية في المالديف : دراسة وصضية وتحليلية في العقائد الدينية والعادات الإجتماعية - مالديفي، آدم شميم بن إبراهيم (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study aims to reveal the reality about the Maldivian religious culture that exists today and how it affects civilized Maldivian society after several centuries since the Maldives embraced Islam. The study sheds light on the religions and traditions that existed before Islam in the region. Furthermore, the study discusses the period in which the Maldives was introduced to Islam and the reasons that led them to accept it. The present study reveals the impact of the ancient religious cultures has had on the Maldivian society today and their relationship with pre-Islamic cultures and traditions of neighbouring countries such as Sri Lanka and India. The researcher visited different regions and islands and conducted personal interviews with both the clerics who have had sovereignty and leadership in those cultures and Maldivian Islamic scholars and their views on those cultures. And then the researcher describes, analyses and explains the reality and rulings. The study describes Maldivian scholars' efforts to change some cultures which contradict Islamic traditions and are against Islamic moral teachings. The study also reveals how they managed to eliminate negative attitudes and cultures from the Maldivian society and how they spread the correct teachings of Islam.